Models of biological parts for synthetic biology design - Mohamed Arshath. (2011)
Modeling has been used in many disciplines i) to gain insights into systems and ii) to reduce complexity through systematic optimization. Synthetic biology, which distinguishes itself from other related fields based on quantification, has also been exploiting modeling to better understand biological systems. In this project, we aim to model our sensing device based on two different methods – Model 1 and Model 2. The sensing device is part of an engineered bacteria that produces GFP upon induction with autoinducer, 3OC12HSL. In Model 1, we used steady-state experimental data to derive important parameters which were used in modeling while in Model 2 the dynamic production of GFP from the experimental data itself was used in deriving those parameters. Parameters were also derived from literature for both models. Using simulation, Model 1 could not capture the dynamic production of GFP without modifying the derived parameters. Model 2 was better at capturing the dynamics and steady state behaviour of the experimental data. Apart from that, we have also annotated all the species or biomolecules that were used in an effort to make our models available for the community.